The Assistant Еducator – a Valuable Resource in the Care, Education and Socialization of Kindergarten Children - Aksenia Tileva (Педагогически форум)
Kindergarten, as an educational institution in which the training, upbringing and socialization of children takes place, is nowadays burdened with high public expectations. The connection between good educational results and children's participation in organized pre-school education is being discussed more and more often. Bulgaria has a pre-school infrastructure that provides a suitable educational environment. Participants in the educational process are children, teachers and parents, but an undervalued resource is the assistant educator. Through their professional duties and their presence in the child's life in the kindergarten, they are not only responsible for maintaining hygiene, but also assist teachers in organizing games, training, meals, walks with the children. Teamwork between teacher and an assistant educator creates a feeling of coziness and tranquility in children, so that each of them can feel included, protected, loved and encouraged in their development. This article presents some opportunities for optimizing the functional duties of assistant educators, as well as for the development of their professional competences. Effective use of such resource would help to increase the quality of the educational process.